2021
DOI: 10.21203/rs.3.rs-783015/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes in Physical Activity, Screen Time, Sleep, and Mental Health of Japanese Young Children: A Longitudinal Study Pre- and During-COVID-19

Abstract: Specialized guidelines are required for the health behaviors of vulnerable populations such as children. This is especially true during the COVID-19 pandemic, wherein major lifestyle changes have occurred, especially among young children. The present study aims to use longitudinal data to understand changes in the physical activity, screen time, sleep, and mental health of preschool-aged children in Japan during the COVID-19 pandemic, compared to pre-pandemic periods. Subjective and objective measures were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Play is also closely related to children’s physical wellbeing. Children are often engaged in physical activities while participating in organized play and dance in daycare, kindergarten, and primary school, and at the playground or park after school [ 3 ]. Play experiences, directly or indirectly, are important for children and have an impact on children’s social and emotional development [ 4 ] as well as academic achievement [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Play is also closely related to children’s physical wellbeing. Children are often engaged in physical activities while participating in organized play and dance in daycare, kindergarten, and primary school, and at the playground or park after school [ 3 ]. Play experiences, directly or indirectly, are important for children and have an impact on children’s social and emotional development [ 4 ] as well as academic achievement [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analytical research showed that the COVID-19 pandemic has exacerbated the mental health of children aged 5–13 years and brought about negative impacts on prosocial behaviors and caused hyperactivity, with greater effect sizes in European compared to Asian populations [ 4 ]. Taking these results at face value, it is critical to implement appropriate strategies in Indonesia that can help increase physical activity; reduce sedentary behavior, including screen time; and ensure that preschool children obtain sufficient sleep during the COVID-19 pandemic to keep longer-term health risks at bay [ 3 ].…”
Section: Introductionmentioning
confidence: 99%